Anisotropic Damage Plasticity Model for Concrete and Its Use in Plastic Hinge Relocation in RC Frames with FRP. (November 2017) - Javanmardi, M.R.; Maheri, Mahmoud R.
Abstract: In an RC frame, relocating plastic hinges in the beam away from the column face is suggested to increase ductility of the frame. This can be achieved through flange-bonded FRP retrofit of the joint. Relocating the plastic hinges further into the beam, shortens the effective length of the beam. As the effective length of the beam is reduced, ductile flexure failure in the beam may switch to a brittle shear failure, resulting in a decrease in ductility of the frame. The consequences and limits of plastic hinge relocation are therefore important issues in need of evaluation. To achieve this, in this paper, an accurate numerical model is first developed for simulating the complex behaviour of concrete and its interaction with steel and FRP materials. For this purpose, anisotropic damage plasticity model for concrete is developed. Damage plasticity model simulates irreversible plastic deformation besides material degradation (crack). After verifying the accuracy of the developed software through comparison with experimental results, response of full-scale RC frames with different beam clear length/effective height ratios is evaluated to find advantages and drawbacks of the flange-bonded retrofitting scheme for relocating plastic hinges. The results show that for beam clear length/height ratios < 6, the frame cannot achieve the 0.02 code-required inelastic drift and the ductile flexural failure in the beam changes to an undesirable brittle shear failure. Also, the results indicate that for clear length/height ratios between 6 and 9, bending moment at the face of the column may increase by up to 60% depending on the length of FRP overlay, therefore, columns should be controlled, and if necessary, be retrofitted for the increased moment.